Inventory distribution problem via stochastic programming. (1st January 2014) - Shiina, Takayuki; Umeda, Masayuki; Imaizumi, Jun; Morito, Susumu; Xu, Chunhui
Previous research on inventory distributions between local warehouses or retailers (bases) has focused separately on either of two types of stock transshipment policies: preventive lateral transshipments or emergency lateral transshipments. Each of these has its advantages and disadvantages, and combining these policies may well enable merchandisers to achieve higher service levels. Thus, the combined use of these policies is the focus of the present study. A stochastic programming problem is formulated with demand as a stochastic variable, and the policy of using both preventive and emergency lateral transshipment is examined for its effectiveness while solution methods are examined for their efficiency.